2020
DOI: 10.1177/0972150920969927
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Credit Risk on Performance: A Case of South African Commercial Banks

Abstract: The objective of the study was to comparatively assess the impact of credit risk on the performance of big and small banks in South Africa. Data from audited financial reports of 14 commercial banks were obtained and divided into two panel data sets and analysed using the R-Studio software version 3.5.1 to assess the impact of capital adequacy ratio (CAR), non-performing loan to gross loan (NPLGL), loan-to-deposit ratio (LTDR), leverage ratio (LR), board gender diversity (BGD), with bank size (total asset) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Another comparison of the impact of CR on the profitability of large and small banks in South Africa indicated that the CR of smaller banks has a more significant effect on performance when proxied by ROA compared to larger banks. However, the CR of smaller banks exhibited a lesser impact on financial performance than larger banks, when measured by ROE during the period from 2008 to 2017 (Lawrence et al, 2020). Furthermore, research reveals that the profitability of the parent bank negatively affects the subsidiary's CR (Škrabić Perić et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Another comparison of the impact of CR on the profitability of large and small banks in South Africa indicated that the CR of smaller banks has a more significant effect on performance when proxied by ROA compared to larger banks. However, the CR of smaller banks exhibited a lesser impact on financial performance than larger banks, when measured by ROE during the period from 2008 to 2017 (Lawrence et al, 2020). Furthermore, research reveals that the profitability of the parent bank negatively affects the subsidiary's CR (Škrabić Perić et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 96%
“…RON-CHF exchange rate turned out to be the main factor affecting an increase in the NPL. Lawrence et al (2020) concluded that NPL, CAR, LR, LTDR and age of banks had a significant and greater impact on the ROA of small banks compared to the big ones. At the same time, NPL ratio affected the ROE of small banks to a relatively lower extent than it did in the case of big credit institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, the number of banks under consideration is relatively small. However, the study took into account the majority of commercial banks that operate in Poland (assets of the banks analysed account for 84.90% of the assets of the banking sector in Poland) as well as some other studies based on relatively small samples, in fact, limited to commercial banks constituting specific banking sectors which is also the case of our research (Hada et al 2020;Lawrence et al 2020). The second limitation is connected with the relatively short horizon of the study.…”
mentioning
confidence: 99%
“…In addition, banks should prioritize female borrowers over males. Lawrence et al (2020) presented the effect of credit risk control on the financial performance of South African banks (i.e., for both big and small banks). For the research, the author collected data from 14 banks and then analyzed them using R-Studio software to evaluate the effect of capital adequacy ratio, non-performing loan to gross loan, loan-todeposit ratio, leverage ratio, board gender diversity, bank size, and age size as the control variables on performance based on return on asset and return on equity.…”
Section: A Credit Risk Control and Profitability Of Microfinance Banksmentioning
confidence: 99%